2023
DOI: 10.1186/s12864-023-09718-2
|View full text |Cite|
|
Sign up to set email alerts
|

Chromosome-level genome assemblies of Cutaneotrichosporon spp. (Trichosporonales, Basidiomycota) reveal imbalanced evolution between nucleotide sequences and chromosome synteny

Yuuki Kobayashi,
Ayane Kayamori,
Keita Aoki
et al.

Abstract: Background Since DNA information was first used in taxonomy, barcode sequences such as the internal transcribed spacer (ITS) region have greatly aided fungal identification; however, a barcode sequence alone is often insufficient. Thus, multi-gene- or whole-genome-based methods were developed. We previously isolated Basidiomycota yeasts classified in the Trichosporonales. Some strains were described as Cutaneotrichosporon cavernicola and C. spelunceum, whereas strain HIS471 remained unidentifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Following publication of the original article [ 1 ], it was reported that part of the figure captions for Figs. 1, 2, 3, 4 and 5 were mistakenly inserted into the article body.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [ 1 ], it was reported that part of the figure captions for Figs. 1, 2, 3, 4 and 5 were mistakenly inserted into the article body.…”
mentioning
confidence: 99%
“…The correct Figs. 1-5 with their captions are given in this Correction article and the original article [ 1 ] has been updated.…”
mentioning
confidence: 99%